Economic evaluation of a medical ambulatory care service using a single group interrupted time‐series design. Issue 2 (26th September 2022) - Pincombe, Aubyn; Schultz, Timothy J.; Hofmann, Dirk; Karnon, Jonathan
Abstract: Rationale: Increasing demand for hospital services can lead to overcrowding and delays in treatment, poorer outcomes and a high cost‐burden. The medical ambulatory care service (MACS) provides out of hospital patient care, including diagnostic and therapeutic interventions for patients that require urgent attention, but which can be safely administered in the ambulatory environment. The programme is yet to be rigorously evaluated. Aims/Objectives: The aim of this study is to evaluate the impact of the MACS programme on emergency department (ED) presentations, hospital admissions, length‐of‐stay and health service costs from a health system perspective. Method: We used a single group interrupted time series methodology with a multiple baseline approach to analyse the impact of the MACS clinic on ED presentations, hospital admissions, length‐of‐stay and cost outcomes for general practitioners (GP)‐referred, ED‐referred and ward‐referred patients under two counterfactual scenarios: an increasing trend in health utilization based on preperiod predictions or a stabilization of utilization rates. Results: The time trend of hospital utilization differed after attending MACS for all three referral groups. The time trend for the GP‐referred group declined significantly by 0.36 ED presentations per 100 patients per 30 days [95% confidence interval (CI): −0.52 to −0.2], while inpatient length of stay declined significantly by 1.56 and 3.70 days, respectively, per 100 ED‐referred and ward‐referred patients per 30 days (95% CI: −2.51 to −0.57 and −5.71 to −1.69,  respectively). Under two different counterfactual scenarios, the predicted net savings for MACS across three patient groups were $78, 685 (95% CI: $54, 807−$102, 563) and $547, 639 (95% CI: $503, 990−$591, 287) per 100 patients over 18 months. Conclusion: MACS was found to be cost‐effective for GP and ward‐referred groups, but the expected impact for ED‐referred patients is sensitive to assumptions. Expansion of the service for GP‐referred patients is expected to reduce hospitalizations the most and generate the largest net cost savings.